Assessment of Caries Prevalence and Related Risk Factors Among a Group of Lebanese Children with Autism Spectrum Disorder: A Case-Control Study - KASSAB, Ranim B.; OSMAN, Aly; TARABAIH, Ahmad (International Arab Journal of Dentistry (IAJD), 2023)
Objectives: The study aimed to assess dental caries prevalence and its associated risk factors for children with Autism Spectrum Disorder (ASD) among different age groups. Material and Methods: Forty-five children with autism aged between 3-16 years matched to 45 healthy children were selected. Children were recruited from autistic centers/schools in Saida, South Lebanon. Each child assessed for caries prevalence and risk factors using DMFT/dmft indices and the WHO standardized questionnaire. Student’s t-test, Pearson’s correlation test, and One Way ANOVA followed by Tukey’s post hoc tests were used. Statistical significance was set at 95%. Result: DMFT/dmft scores in non-ASD group were 0.85±1.53 and 2.15± 3.03 respectively and in ASD group were 0.72±1.34 and 1.87±3.09 respectively with no significant difference in both groups (p>0.05). Conclusion: Preventive dental programs targeting autistic children and their parents/caregivers are needed to enhance their oral health status and general well-being.